2013
DOI: 10.1007/s13762-013-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microbial communities in a granular activated carbon–sand dual media filter for drinking water treatment

Abstract: Modification of conventional rapid sand filter into granular activated carbon-sand dual media filter has become increasingly attractive to drinking water producers in many Chinese urban regions. In this study, a pilot-scale dual media filter was constructed to monitor its performance. The operational results indicated that the dual media filter performed well both on nitrification and on reduction of chemical oxygen demand. Microbial community structures at different sampling sites were also compared using 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
1
28
1
1
Order By: Relevance
“…The dominance of Proteobacteria has been found in natural wetlands (Ansola et al 2014;Liu et al 2014b), wastewater CW systems (Ansola et al 2014;Bouali et al 2014;Huang et al 2013), and biofilters treating surface water (Feng et al 2013a;Liao et al 2013b). Moreover, a previous study using DGGE analysis also suggested the dominance of proteobacterial organisms in a large-scale CW system Fig.…”
Section: Bacterial Community Structurementioning
confidence: 88%
“…The dominance of Proteobacteria has been found in natural wetlands (Ansola et al 2014;Liu et al 2014b), wastewater CW systems (Ansola et al 2014;Bouali et al 2014;Huang et al 2013), and biofilters treating surface water (Feng et al 2013a;Liao et al 2013b). Moreover, a previous study using DGGE analysis also suggested the dominance of proteobacterial organisms in a large-scale CW system Fig.…”
Section: Bacterial Community Structurementioning
confidence: 88%
“…Based on the significant difference between bacterial communities in raw water and on BAC, Soonglerdsongpha et al (2011) suggested that bacterial community structure changed along the BAC filtration process. Previous studies showed the shift of bacterial community structure inside BAC systems (Liao et al 2012(Liao et al , 2013) and granular activated carbon-sand dual media filter (Feng et al 2013a). However, an earlier work using culture-dependent method indicated that BAC filtration did not change the nature of the bacterial populations associated with drinking water (Burlingame et al 1986).…”
Section: Bacterial Community Structuresmentioning
confidence: 98%
“…Feng et al (2013b) found that Nitrospirae and Alphaproteobacteria were the dominant bacterial groups in a full-scale drinking water biosand filter. Nitrospirae, Alphaproteobacteria, Acidobacteria, and Betaproteobacteria were the dominant groups in a granular activated carbonsand dual media filter for drinking water treatment (Feng et al 2013a). Li et al (2010) found that Betaproteobacteria was the most abundant bacterial group both in bench-scale and pilot-scale BAC reactors.…”
Section: Bacterial Community Structuresmentioning
confidence: 99%
“…N-Nitrosamines are a class of highly carcinogenic NDBPs and are commonly detected in drinking water. Drinking water biofilters have been widely used to remove natural and anthropogenic organic matter, inorganic nitrogen compounds and particulates (Feng et al 2013a;Liao et al 2013a;Liu et al 2012a). Biofiltration might be an effective way to minimize the formation of N-nitrosamines in drinking water (Kristiana et al 2013).…”
Section: Introductionmentioning
confidence: 99%